(3QSGdI aj GdCbjSI GdefWbjIs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; Chd HOA GdCeQ GdCSfi GSe PQC hHQC GdBNQI hGdChdi hBNQ eG fWb aj GdHQRN GdCSei hdeG habfj Gddg HePGcQI MGTjI GdejQ Ydi GdLdGd Ydi JgPjH GdSYO GdOjf (B( (3cPG (B) (3GdJaJRGfj CQOJ EjQGO eG SfM hJMQjQ eG CTgQ hCQLM aCbhd hHGddg GdJhajb s
(3BNQgG (B:s
(3hCeG EPG VQHfG CaQGO GdCbjSI GdhGbYI aj GdhLhg GdCQHYI ef GdGMJeGdGJ GdJSY aj GdMGUd ef TQH GdGKfjf aj GdKeGfjI hgh SJI YTQ ELeGdG dG jMUd eGFI hCQHYI hCQHYhf GMJeGdG aj bVjI GdHSedI s
(3JJdhg fbhdGJs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs